Physical Properties, Health Functionality, and Sensory Evaluation of Bread with the Unused Parts of Waxy Barley - Tsugumi Furuichi; Ayane Uno; Yoko Tsurunaga (Applied Sciences)
In Japan, rising demand for waxy barley has led to concerns over bran waste. We investigated the effects of replacing wheat flour with different proportions of the waxy variety ‘Kirarimochi’ barley bran on the physical properties and health functionality of the bread. We used both the inner bran layer (IBLP) and outer bran layer (OBLP) of waxy barley as replacement sources and tested their effects on the appearance, height, specific volume, β-glucan, antioxidant properties, physical and sensory properties of bread. Bread with a 10% IBLP replacement group showed significantly increased height, specific volume, and softness compared to the control, indicating that IBLP at this level serves as an effective enhancer of bread volume and texture. At higher replacement levels (30–50% IBLP), the breads exhibited increased β-glucan content and enhanced antioxidant properties. Sensory evaluation revealed a stronger aroma, increased moistness, and stickiness of bread with 50% IBLP substitutions. OBLP was not suitable for sensory evaluation. These results show that IBLP can improve the specific volume and texture of bread and enhance its health functional components by adjusting the ratio. It also provides a clue to solving the problem of bran disposal.